Cinematic rendering in rheumatic diseases—Photorealistic depiction of pathologies improves disease understanding for patients - Pachowsky, Milena L.; Morf, Harriet; Simon, David; Schönau, Verena; Valor-Mendez, Larissa; Knitza, Johannes; Fagni, Filippo; Engel, Klaus; Uder, Michael; Hueber, Axel; Schmidkonz, Christian; Schett, Georg; et al. (Frontiers in Medicine, 2022)
Background: Patient education is crucial for successful chronic disease management. Current education material for rheumatic patients rarely includes images of disease pathologies, limiting patients’ disease understanding. Cinematic rendering (CR) is a new tool that allows segmentation of standard medical images into pictures that illustrate disease pathologies in a photorealistic way. Thus CR has the potential to simplify and improve the explanation of disease pathologies, disease activity and disease consequences and could therefore be a valuable tool to effectively educate and inform patients about their rheumatic and musculoskeletal disease (RMD). Objectives: To examine the feasibility of creating photorealistic images using CR from RMD patients depicting typical rheumatic disease pathologies and, in a second step to investigate the patient-perceived educational potential of these photorealistic images in clinical routine. Methods: We selected conventional, high-resolution (HR) and positron emission tomography (PET) computed tomography (CT) images of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), axial spondyloarthritis (axSpa) and giant cell arteritis (GCA) that showed typical respective disease pathologies. These images were segmented using CR technique. In a prospective study, physicians used CR-enhanced and conventional original images to explain the depicted pathognomonic pathologies to patients with the respective disease. Patients were then asked to complete a questionnaire evaluating the perceived usefulness of being presented with CR-enhanced images to better understand their underlying disease. Results: CR images were successfully generated from above mentioned CT methods. Pathologies such as bone erosions, bone loss, ankylosis and PET-based inflammation could be visualized in photorealistic detail. 79 patients (61% females, mean age 55.4 ± 12.6 y; RA 29%, PsA 29%, axSpA 24%, GCA 18%) were interviewed and answered the quantitative questionnaire. Irrespective of disease, all patients agreed or highly agreed that CR-based images help to improve disease understanding, should be shown at disease onset, provide a rationale to regularly take medication and would like to have access to their own CR-enhanced images. Conclusion: Conventional disease images can successfully be turned into photorealistic disease depictions using CR. Patients perceived CR images as a valuable addition to current patient education, enabling personalized disease education and potentially increased medication adherence